Molecular regulation of urea cycle function by the liver glucocorticoid receptor - Okun, Jürgen G.; Conway, Sean; Schmidt, Kathrin V.; Schumacher, Jonas; Wang, Xiaoyue; Guia, Roldan M. de; Zota, Annika; Klement, Johanna; Seibert, Oksana; Peters, Achim; Maida, Adriano; Herzig, Stephan; et al. (Molecular metabolism, 2015)
Objective - One of the major side effects of glucocorticoid (GC) treatment is lean tissue wasting, indicating a prominent role in systemic amino acid metabolism. In order to uncover a novel aspect of GCs and their intracellular-receptor, the glucocorticoid receptor (GR), on metabolic control, we conducted amino acid and acylcarnitine profiling in human and mouse models of GC/GR gain- and loss-of-function. - Methods - Blood serum and tissue metabolite levels were determined in Human Addison's disease (AD) patients as well as in mouse models of systemic and liver-specific GR loss-of-function (AAV-miR-GR) with or without dexamethasone (DEX) treatments. Body composition and neuromuscular and metabolic function tests were conducted in vivo and ex vivo, the latter using precision cut liver slices. - Results - A serum metabolite signature of impaired urea cycle function (i.e. higher [ARG]:[ORN + CIT]) was observed in human (CTRL: 0.45 ± 0.03, AD: 1.29 ± 0.04; p < 0.001) and mouse (AAV-miR-NC: 0.97 ± 0.13, AAV-miR-GR: 2.20 ± 0.19; p < 0.001) GC/GR loss-of-function, with similar patterns also observed in liver. Serum urea levels were consistently affected by GC/GR gain- (∼+32%) and loss (∼−30%) -of-function. Combined liver-specific GR loss-of-function with DEX treatment revealed a tissue-autonomous role for the GR to coordinate an upregulation of liver urea production rate in vivo and ex vivo, and prevent hyperammonaemia and associated neuromuscular dysfunction in vivo. Liver mRNA expression profiling and GR-cistrome mining identified Arginase I (ARG1) a urea cycle gene targeted by the liver GR. - Conclusions - The liver GR controls systemic and liver urea cycle function by transcriptional regulation of ARG1 expression.